If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6t + -7)(t + 6) = 0 Reorder the terms: (-7 + 6t)(t + 6) = 0 Reorder the terms: (-7 + 6t)(6 + t) = 0 Multiply (-7 + 6t) * (6 + t) (-7(6 + t) + 6t * (6 + t)) = 0 ((6 * -7 + t * -7) + 6t * (6 + t)) = 0 ((-42 + -7t) + 6t * (6 + t)) = 0 (-42 + -7t + (6 * 6t + t * 6t)) = 0 (-42 + -7t + (36t + 6t2)) = 0 Combine like terms: -7t + 36t = 29t (-42 + 29t + 6t2) = 0 Solving -42 + 29t + 6t2 = 0 Solving for variable 't'. Factor a trinomial. (-6 + -1t)(7 + -6t) = 0Subproblem 1
Set the factor '(-6 + -1t)' equal to zero and attempt to solve: Simplifying -6 + -1t = 0 Solving -6 + -1t = 0 Move all terms containing t to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1t = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1t = 0 + 6 -1t = 0 + 6 Combine like terms: 0 + 6 = 6 -1t = 6 Divide each side by '-1'. t = -6 Simplifying t = -6Subproblem 2
Set the factor '(7 + -6t)' equal to zero and attempt to solve: Simplifying 7 + -6t = 0 Solving 7 + -6t = 0 Move all terms containing t to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -6t = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -6t = 0 + -7 -6t = 0 + -7 Combine like terms: 0 + -7 = -7 -6t = -7 Divide each side by '-6'. t = 1.166666667 Simplifying t = 1.166666667Solution
t = {-6, 1.166666667}
| log(2t+4)=log(13-3t) | | 20+b-b^2=0 | | 11x+4.4=8 | | (6x+1)(x+2)=0 | | x=4(x-1)+1 | | y=2cos(x^2) | | 6x+28=2x+52 | | x^2+6x+8=o | | 5s+s^2+4=0 | | lnx-ln(x+4)=2 | | 5x-5x=-24 | | 4n^2-48n+144=0 | | -(n+3)=-3+3n | | 7x+65=2x+45 | | (n-5)(8n-7)=0 | | x=1.3 | | 13x-41=180 | | 7(4y-5)+3(4y+6)= | | 8n^2-80n+200=0 | | -x/3=x/3+52 | | 5x/7=x/7+644 | | (7p-9)(9p+5)=0 | | 60=12+6(n-1) | | 2x(x-4)=-14x+8 | | 6x+27+3x+54=180 | | -17-5p=5(2+4p)+2p | | -58.75-x/8=7x/8+191.25 | | 14b-13b+3b=20 | | u(6u-7)=0 | | 4ln(7x)=16 | | -17-5p=5(2+4)+2p | | 3x^3-2x^2-12x+18=0 |